Fracture Mechanics-Based Modelling of Tool Wear in Machining Ti6Al4V Considering the Microstructure of Cemented Carbide Tools - Hossein Gohari; Bin Shi; M. Helmi Attia; Rachid M’Saoubi (Journal of Machine Engineering)
This study introduces a new wear model that can predict tool life in the milling process of Ti6Al4V using a cemented carbide tool. The model uses a finite element (FE) simulation to predict crack growth in the tool material microstructure. The FE model evaluates the crack propagation rate based on the real microstructure of the tool material, which is captured from microscopic images. To determine the normal and tangential forces operating on the flank face, an experimental procedure was developed based on three different flank wear widths. The FE model utilizes the elastic and fracture properties of tungsten carbide, and the elastic-plastic and fracture characteristics of cobalt binder to determine crack growth under the applied cutting forces. The crack propagation information combined with cutting conditions and the initial wear level are used to estimate the tool wear state. The developed model can predict tool life under different cutting conditions, tool geometries, and microstructure properties. Analysis of results showed that the error for the straight cuts was less than 6%, while for the complex cuts, it reached up to 20%. The accuracy of the model can be improved by extending the calibration test to higher levels of flank wear.